Data Mining Market Basket Analysis Menggunakan Algoritma Hash Based Pada Sistem Penjualan Produk - M Fadli Hamdi Lubis (SNASTIKOM, 2023)
This research aims to determine consumer shopping patterns with Data Mining Market Basket Analysis using the Hash Based Algorithm in the product sales system. The results show that the most purchased item based on the period August 2022 - July 2023 for 1-itemset is Sanger Ice (A) at 42% . For 2-itemset, namely Sanger Ice (A) and Sanger Hot (B), it is 25%. After three iterations, one address remains in the 3-itemset hash table. Frequent itemsets obtained are Sanger Ice (A), Sanger Hot (B), Bird's Nest (AO) with a quantity sold of 42 (Support Count) or 12% and Confidence 49%